Recurrence of mass reproduction of sugar beet pests in Ukraine - Диченко, О. Ю. (Scientific Progress & Innovations, 2012)
Recurrence of mass reproduction of sugar beet pests has been studied. Investigations proved that mass reproduction of sugar beet pests was observed cyclically rather than periodically. Synchronism of population cycles with sudden changes of of solar activity has been snown. Solar activity is recommended to use for prediction of the beginning of next mass reproduction.